No evidence of other‐race effect for Chinese faces in Malaysian non‐Chinese population. Issue 1 (6th November 2019) - Estudillo, Alejandro J.; Lee, Jasmine Kar Wye; Mennie, Neil; Burns, Edwin
Summary: The other‐race effect (ORE) reflects poor recognition of faces of a different race to one's own. According to the expertise‐individuation hypothesis, this phenomenon is a consequence of limited experience with other‐race faces. Thus, similar experience with own and other‐race faces should abolish the ORE. This study explores the ORE in a multi‐racial country (i.e., Malaysia) by comparing Malaysian observers' face recognition for faces of a predominant racial group in Malaysia (i.e., Chinese) with faces from an uncommon group (i.e., Caucasian). Malaysian Chinese, Malays, and Malaysian Indians completed the Cambridge Face Memory Test (CFMT) and the CFMT‐Chinese. Compared with the normative scores, Malaysian observers showed poor performance in the CFMT‐Caucasian. Interestingly, Malays and Malaysian Indians observers' performance was identical to that of Malaysian Chinese in the CFMT‐Chinese and to the normative scores of the test. These results demonstrate the relevance of experience in shaping the ORE.